Possession, relative title, and ownership in English law - Rostill, Luke David (Oxford University Press, 2021)
This monograph provides a sustained analysis of two foundational principles of English property law: the principle of relative title and the principle that possession is a source of title. It examines several central concepts in the law of property, including possession and ownership.